Identifikace a biochemická charakterizace lektinů v hemolymfě tří druhů klíšťat rodu Rhipicephalus - Fišer, Miroslav (Jihočeská univerzita, 2009)
Lectins are tissue specific carbohydrate binding proteins with possible functions in invertebrate immunity and pathogen transmission. The main goal of this study was to identify hemolymph lectins in three different tick species. Three proteins with molecular weights of 58 kDa, 75 kDa and 180 kDa were detected in all investigated species using antibodies directed against hemagglutination activity of Rhipicephalus appendiculatus hemolymph. These proteins were characterized by biochemical methods such as Schiff/periodate staining, lectin blotting, enzymatic deglycosylation, hemagglutination analysis, immunoblotting, and mass spectrometry.
Identification and biochemical characterization of lectins in the hemolymph of three species of tick in the genus Rhipicephalus
Keywords: lektin; hemolymfa; klíště; Rhipicephalus; glykosylace; lectin; hemolymph; tick; Rhipicephalus; glycosylation